2006
DOI: 10.4040/jkan.2006.36.5.732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-nutritive Sucking on the Physiological and Behavioral States of Pre-term Infants during Tube Feeding

Abstract: This result suggests non-nutritive sucking by using a pacifier is an effective intervention for pre-term infants during tube feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…14 Several patterns of oral intervention are used separately and in combination, including NNS, oral massage, and sensorial-motor stimulation. [21][22][23] The details of the process as well as the frequency of application differ considerably among intervention methods. Oral intervention combined with NNS was adopted by Fucile et al and showed a definite effect on sucking-swallow-respiration function, especially when administered only once per day, which is very clinically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several patterns of oral intervention are used separately and in combination, including NNS, oral massage, and sensorial-motor stimulation. [21][22][23] The details of the process as well as the frequency of application differ considerably among intervention methods. Oral intervention combined with NNS was adopted by Fucile et al and showed a definite effect on sucking-swallow-respiration function, especially when administered only once per day, which is very clinically feasible.…”
Section: Discussionmentioning
confidence: 99%